Educative Intervention for parents or Tutors of asthmatic children - Eneida Bravo Polanco; Beatríz Pérez García; Narciso Águila Rodríguez; Dalia Rosa Ruiz Roja; Yoanka Torres López; Mayelín Martínez Santana (Medisur)
Foundation: in Cuba, bronchial asthma constitutes an important health problem with relevant incidence in children. Parent´s knowledge about its management results essential. Objective: to apply a program of educative intervention to increase the level of information of parents and children. Methods: intervention study developed from May 2016, in doctor´s office 8 Cumanayagua. All parents whose children had been diagnosed bronchial asthma in ages from 0 to 15 were included. A diagnosis was realized to identify the level of information about the management of bronchial asthma and on those bases four educative topics were prepared to be taught to parents. After the intervention it was it was checked the level of assimilation. The variables measured were age and sex of the children, knowledge of parents about symptom identification, management and measures for its prevention, precipitating factors. Results: the male sex predominated among children (72%) and ages from 5-9 (54,6%). Initial diagnosis showed that parents and tutors had a low level of information about bronchial asthma, 63, 5 % was evaluated poor or low. The biggest gaps were on the prodromal symptoms of asthma (63, 64 % low), figures that were reduced to 9% and 0% respectively after the intervention. Precipitating factors for crisis mostly identified were tobacco smoke, respiratory infections, climate changes and the least known emotional experiences. A high knowledge of preventive measures was elevated from 9.09% to 81,82 % after the intervention. Educative actions increased the percentage of those evaluated good in knowledge which went up to 81,82 %. Conclusion: not all parents of asthmatic children have adequate knowledge about the management of their children, which may be modified by applying strategies to educate them.